Gangguan Bahasa dan Implikasinya terhadap Pembelajaran: Kajian Neourolinguistik pada Disleksia dan Gagap - Hariyanti; Shofiyah; Anwar Sidik (Journal of Social, Educational and Religious Studies, 2026)
This study aims to analyze language disorders in children, particularly dyslexia and stuttering, from neurolinguistic and psycholinguistic perspectives. A qualitative approach with a library research design was employed by reviewing relevant books, journal articles, and previous studies. The findings indicate that children’s language abilities are closely related to the integrated functioning of various brain areas responsible for phonological processing, visual–auditory integration, and speech production. Disruptions in these neurological systems can lead to language disorders, especially dyslexia and stuttering. Dyslexia is identified as a written language disorder caused by differences in the structure and function of brain regions involved in phonological processing, resulting in difficulties in reading, writing, and spelling despite normal intelligence levels. Meanwhile, stuttering is a speech fluency disorder characterized by sound repetitions, sound prolongations, and speech blocks due to instability in speech motor control, disrupted speech rhythm, and inefficient speech feedback mechanisms. The neurolinguistic approach provides a comprehensive understanding of language disorder mechanisms by integrating neurological, psycholinguistic, and pedagogical aspects and serves as a foundation for developing more effective intervention strategies. Phonological and multisensory interventions are recommended for dyslexia, while fluency training, desensitization techniques, and emotional regulation are recommended for stuttering. Future research is encouraged to develop empirical and interdisciplinary studies to strengthen the implementation of neurolinguistic approaches in language learning and therapy for children.